Felicità e benessere Una ricognizione critica - corsi, cecilia (Studi e saggi, 2015)
This volume sets the start for the Quaderni "Cesare Alfieri", commissioned by the Council of the School of Political Sciences of the University of Florence as a scientific and editorial project aimed at involving all the cultural components animating the School. This work is an attempt to create an occasion of dialogue, research to deepen the acquired knowledge and investigate complex social issues from different points of view. For this first Quaderno - or notebook - the Scientific Committee has decided to focus on the concept of "well-being", to observe it from different perspectives and to relate it to the notion of happiness. The survey aims to offer food for thought, some lines for a path, different views on a theme that constitutes one of the great knots that our democracies must face: the well-being to be conquered, especially in the twentieth century, a real challenge for the beginning of a new Millennium.